Produção e qualidade de mudas de morangueiro com diferentes concentrações de nitrogênio em cultivo sem solo - Oliveira, Clarisse Silva (2009)
The objective of this study was to evaluate the effect of nitrogen concentration on the production and quality of strawberry bare root transplants and runner tips in a soilless growing system using sand as substrate. Stock plants were planted on September 13th, 2007. Transplants were harvested on February 18th, 2008. Treatments were nitrogen concentrations in the nutrient solution of 8, 11, 14 and 17 mmol L-1. The experiment was a completely randomized design with three replications of 3.6m2 plots. Number and crown diameter of bare root transplants and number of runner tips were evaluated at harvesting. Number of bare root transplants and runner tips was not affected by N concentration in the nutrient solution. An average of 339 bare root transplants and 836 runner tips were harvest per stock plant. Crown diameter of bare root transplants decreased linearly with the increase in N concentration of the nutrient solution. It was concluded that in this soilless cropping system the increase in N concentration in the nutrient solution does not affect the number of strawberry bare root transplants and runner tips, but the crown diameter of bare root transplants is reduced. The N concentration of 8 mmol L-1 may be used for crop propagation in this growing system.